New Trilacuna species from Thailand, Malaysia and Sumatra (Araneae, Oonopidae) - Eichenberger, Beata; Kranz-Baltensperger, Yvonne (Zootaxa, 2011)
The genus Trilacuna (Araneae, Oonopidae), comprising only two species from China, is supplemented by seven new species collected in Thailand, Malaysia and Sumatra (T. merapi, T. bilingua, T. clarissa, T. werni, T. alces, T. kropfi, and T. diabolica). The new species exhibit an incised labium and a complicated set of membranes and/or filiform projections around the embolus, both diagnostic for the genus Trilacuna.